Analysis of Factors Related to Stunting Among Children Aged 6-24 Months in Central Jakarta - Dyah Woro Kartiko Kusumo Wardani; Eviyani Margaretha Manungkalit (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Stunting is a condition in which children aged 0-5 years have height-for-age with a z-score of below -2SD based on growth standards according to WHO, which occurs at the age of 0-5 years. Stunting condition may result in the inhibition of cognitive and motor development so as to create a generation that is less competitive and have disrupted metabolic system and they are at risk of various diseases. The causes of stunting are multi-dimensional factors such as birth length and genetics, maternal height, economic status, level of education and child care patterns. This study aims to analyze factors related to the incidence of stunting among children aged 6-24 months in Central Jakarta with a cross sectional study using a questionnaire. Data were analyzed using Chi-square and multiple logistic regression tests. The results showed that there was no relationship between education, age, family income, gestational age, BMI, newborn length and exclusive breastfeeding with stunting (P>0.05). In contrast, there was a relationship between maternal height and stunting (p <0.05). Furthermore, the results of regression test showed that the most dominant influential factor on the incidence of stunting was maternal height.